As ações de extensão como prática formativa dos alunos do ensino médio integrado e superior do IFFar – campus São Borja - Flores, Laiane Frescura (2019)
The research was conducted under the Professional Master in Public Policy and Educational Management in the line "Public Policy and Management of Basic and Higher Education", Federal University of Santa Maria. It deals with the contributions of the extension actions of the Federal Institute Farroupilha - Campus São Borja, as a formative practice of the students of integrated and superior high school. The Institution's mission is to promote public and free professional, scientific and technological education courses through teaching, research and extension, focusing on integral citizen education and sustainable development. The objective is to analyze the contributions to the academic and professional formation of the student who works in extension actions in the referred Campus. In this sense, this research was conducted with 30 students who participated in extension actions in 2017 and 2018. The methodology used was characterized as a qualitative and quantitative research, under case study, through questionnaires and interviews and the analysis. The data was obtained through the Content Analysis technique. The data construction instruments were: bibliographic research, participant observation, document analysis, google forms questionnaires and semi-structured interviews. The research participants were students participating in extension actions and servants who acted as coordinators. The results showed that these extension actions are relevant and significant for the students, since they act effectively in the academic, professional, as well as in the human and citizen formation of those involved. It can be observed that the interaction and interaction with the public of the communities and institutions served, provided students with the construction and improvement of skills, personal and professional growth, incorporation of new practices, exchange of experiences, critical view of reality and inequalities, teamwork, event participation and scientific production possibilities. As an academic product, a self-assessment report was generated for students participating in extension actions. This evaluation report will allow the Institution to build qualitative and quantitative indicators about the potentialities and weaknesses related to students' participation in extension actions, listing the contributions to the teaching-learning process. It was concluded that extension actions provide training and a differentiated curriculum, qualifying scientific and popular knowledge, promoting social transformation.